Indentation and scratch testing of a WC-6%wtCo cemented carbide: Corrosion effects on load-bearing capability and induced damage. Issue 11 (1st August 2020) - Zheng, Y.F.; Fargas, G.; Lavigne, O.; Llanes, L.
Abstract: In this work, corrosion effects on the indentation and scratch response of a WC-6%Co hardmetal are investigated. Experimental variables include relative long corrosion times as well as indentation and scratch testing conditions yielding damage scenarios whose depths are similar to length scale of the degraded surface layers. It is found that load-bearing capability and crack extension resistance of the cemented carbide grade studied are significantly reduced after exposure to corrosive media. This is related to relevant changes within the microstructural assemblage of the material, from an effective bulk ceramic-metal composite into a porous layer consisting of a binderless carbide network on top of a pristine-like hardmetal substrate. However, such lessening effects are found to be dependent on the ratio between indentation and/or scratch depth and thickness of the corroded layer. Hence, relative changes decrease as corrosion time increases, and no differences are discerned after seven days of immersion. Similar pronounced corrosion influence is evidenced in surface and subsurface damage scenario resulting after indentation and scratch tests. In this regard, a transition from well-defined cracking systems into a scenario consisting of multiple, branched and less shallow fissures is evidenced when comparing pristine and corroded specimens respectively. The experimental fact that referred cracking features for corroded specimens are confined within the porous-like degraded layers points out that it is the result of small length-scale interaction between cracks and the cavities within the binderless WC skeleton, left after the metallic binder has been leached away.